Antioxidant activity of PLA/PCL films loaded with thymol and/or carvacrol using scCO2 for active food packaging. (December 2020) - Lukic, Ivana; Vulic, Jelena; Ivanovic, Jasna
Highlights: Thymol, carvacrol and their mixture loaded PLA/PCL films using supercritical CO2 . PLA-5 film impregnated with the mixture of thymol and carvacrol showed the best antioxidant activity. Structural, morphological and mechanical properties of films were also analyzed. The slow release into distilled water over longer time (6 weeks) was observed. Abstract: Present study was aimed to produce biodegradable films with antioxidant activity for active food packaging. Films of poly(lactic acid) (PLA) with 5 wt% of poly(ε-caprolactone) (PCL), denoted as PLA-5, were loaded with thymol, carvacrol and their mixture using supercritical CO2 at 40 °C and 10 MPa for 5 h, with 27.53, 21.18, and 21.49 % of loading achieved, respectively. Morphological, structural and mechanical properties of the obtained PLA-5 films were analyzed. The highest total polyphenol content and the best antioxidant activity as well as good storage stability, acceptable physical properties and the lowest release rate (44.51 mg/L released after 6 weeks) were observed for PLA-5 film loaded with thymol and carvacrol mixture. Mixture of thymol and carvacrol loaded into PLA-5 film showed synergy and low percentage of migration into distilled water, revealing great potential for application as a food packaging material with aim to decrease requirements for amount of the active ingredients.